Transcriptional Regulation of Rex1 (zfp42) in Normal Prostate Epithelial Cells and Prostate Cancer Cells - Lee, Mi-Young (2010)
Rex1 (zfp42) was identified by our laboratory because of its reduced expression in F9 teratocarcinoma stem cells after retinoic acid (RA) treatment. The Rex1 (Zfp42) gene is currently widely used as a marker of embryonic stem cells. We compared the transcriptional regulation of the human Rex1 gene in NTera-2 (NT-2) human teratocarcinoma, normal human prostate epithelial cells (PrEC), and prostate cancer cells (PC-3) by promoter/luciferase analyses. Oct4, Sox2, Nanog, and Dax1 transcripts are expressed at higher levels in NT-2 and PrEC cells than in PC-3 cells. Co-transfection analyses showed that YY1 and Rex1 are positive regulators of hRex1 transcription in NT-2 and PrEC cells, whereas Nanog is not. Serial deletion constructs of the hRex1 promoter were created and analyzed, by which we identified a potential negative regulatory site that is located between -1kb to -0.4 kb of the hRex1 promoter. We also delineated regions of the hRex1 promoter between -0.4 kb and the TSS that, when mutated, reduced transcriptional activation; these are putative Rex1 binding sites. Mutation of a putative Rex1 binding site in electrophoretic mobility shift assays (EMSA) resulted in reduced protein binding. Taken together, our results indicate that hRex1 binds to the hRex1 promoter region at -298 bp and positively regulates hRex1 transcription, but that this regulation is lost in PC-3 human prostate cancer cells. This lack of positive transcriptional regulation by the hRex1 protein may be responsible for the lack of Rex1 expression in PC-3 prostate cancer cells.